2008
DOI: 10.1007/s12272-001-1182-9
|View full text |Cite
|
Sign up to set email alerts
|

KR-31762, a novel KATP channel opener, exerts cardioprotective effects by opening SarcKATP channels in rat models of ischemia/reperfusion-induced heart injury

Abstract: The cardioprotective effects of KR-31762, a newly synthesized K+(ATP) opener, were evaluated in rat models of ischemia/reperfusion (I/R) heart injury. In isolated rat hearts subjected to 30-min global ischemia followed by 30-min reperfusion, KR-31762 (3 and 10 microM) significantly increased the left ventricular developed pressure (LVDP) and double product (heart rate x LVDP) after 30-min reperfusion in a concentration-dependent manner, while decreasing the left ventricular end-diastolic pressure (LVEDP). KR-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 26 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…The results from the present study demonstrated that KR-31761 exerts potent cardioprotective activity in rat models of ischemia / reperfusion-induced heart injury through opening K + ATP channels located both at the mitochondria (mitoK + ATP channel) and sarcolemma (sarcK + ATP channel) of cardiomyocytes, unlike its diastereomer KR-31762 (27), with a markedly weaker vasodilating activity compared with BMS-180448, a prototype cardioselective mitoK + ATP -channel opener that does not induce shortening of action potential duration within its cardioprotective concentration (14).…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…The results from the present study demonstrated that KR-31761 exerts potent cardioprotective activity in rat models of ischemia / reperfusion-induced heart injury through opening K + ATP channels located both at the mitochondria (mitoK + ATP channel) and sarcolemma (sarcK + ATP channel) of cardiomyocytes, unlike its diastereomer KR-31762 (27), with a markedly weaker vasodilating activity compared with BMS-180448, a prototype cardioselective mitoK + ATP -channel opener that does not induce shortening of action potential duration within its cardioprotective concentration (14).…”
Section: Discussionmentioning
confidence: 59%
“…KR-31762 was found to have a very weak vasorelaxant activity similar to KR-31761 and significant preischemic cardiodepressant activity, the latter being closely associated with the significant cardioprotective activity against ischemia / reperfusion-induced heart injury (27). The stereospecific relationships of these two diastereomers to their pharmacological features indicate the importance of this functional group as a critical structural determinant of their specificity for mitoK + ATP and sarcK + ATP channels.…”
Section: +mentioning
confidence: 90%
See 2 more Smart Citations
“…For example, diazoxide stimulates all K ATP channel containing SUR1, SUR2A (in the presence of Mg 2+ ADP), and SUR2B. However, Kir6.2/SUR2A channels are only weakly activated by diazoxide in the absence of ADP (D'Hahan et al, 1999;Lee et al;2008). Pinacidil and cromakalim preferentially activate SUR2A and SUR2B, instead of SUR1 (Seino and Miki, 2003).…”
Section: K Atp Channel Activatorsmentioning
confidence: 99%